2019
DOI: 10.1155/2019/1242979
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Cells Express Markers Associated with Immunosurveillance

Abstract: Cervical cancer is the second most frequent cancer in women in Mexico, and its development depends on the presence of human papillomaviruses in the uterine cervix. These oncogenic viruses transform cells where the control over cell cycle disappears, and the capacity to induce apoptosis is absent. On the other hand, some mutations confer to the transformed cells the ability to evade recognition by the immune system. The expression of markers of the immune system such as CD95, MICA/B, CD39, CD73, NKp30, NKp46, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…34,36 In line with this suggestion, the levels of HCP5 were signifi- receptors on their own surface. 30,31,[37][38][39] It is possible that one mechanism by which rs2844511 could modify cervical cancer risk is the regulation of MICA expression and subsequent immune-surveillance of tumor cells. From the results of our study, the risk allele of rs2844511 associated with increased MICA levels in HPV negative (normal) cervical epithelium, but this was reversed in HPV infected cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,36 In line with this suggestion, the levels of HCP5 were signifi- receptors on their own surface. 30,31,[37][38][39] It is possible that one mechanism by which rs2844511 could modify cervical cancer risk is the regulation of MICA expression and subsequent immune-surveillance of tumor cells. From the results of our study, the risk allele of rs2844511 associated with increased MICA levels in HPV negative (normal) cervical epithelium, but this was reversed in HPV infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Little surface expression of MICA is seen in healthy cells; however, most epithelial tumor cells express MICA. There are multiple modes through which cervical cancer cells evolve to evade this detection, including the secretion of MICA in a soluble form to block NKG2D receptors or the aberrant expression of NKG2D receptors on their own surface 30,31,37‐39 . It is possible that one mechanism by which rs2844511 could modify cervical cancer risk is the regulation of MICA expression and subsequent immune‐surveillance of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our group demonstrated that cervical tumour cells express NK cells markers such as NKG2D, NKG2A, NKp30, NKp46 mainly. However, we do not know why cervical cancer cells express these molecules and the benefit they bring to tumour cells regarding NK cells activity (Figure 3) [35,[53][54][55][56][57][58][59][60][61][62].…”
Section: Modulation Of the Nk Cells Response In Cervical Cancermentioning
confidence: 99%
“…These were as follows: (a) MICA/B and CD95 (involved in tumour cell recognition); (b) CD39, CD73, CTLA‐4 (immune system escape); and (c) NKp30, NKp46, NKG2A and KIR3DL1 (typical markers of NK cells like). The authors concluded that these molecules might allow the CCLs to mimic the immune system 71 …”
Section: Cervical Cancer and Its Cell Linesmentioning
confidence: 99%